The Ambiguities of Alcohol: Deviance, Drinking and Meaning in a Canadian Native Community - Shavishinsky, Joel S. (Anthropologica, 2022)
The interplay of Western and Native cultures gives drinking both positive and negative meanings for Indian people. This essay examines the ambiguities of alcohol in one northern Native community, with specific attention given to the way in which drinking relates to deviance and Indian cultural values. It is based largely on fieldwork conducted in the small Dene community of Colville Lake during 1967, 1968 and 1971.